Differential structures in lie superalgebras - Daletskii, Yu. L.; Kushnerevich, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We develop a formal construction of an U-system as a fundamental concept of noncommutative differential geometry. By using the notion of “conditional differential” (an analog of the Hamiltonian mapping), we construct a series of brackets that generalize the classical Poisson brackets.